Early-onset pancreatic cancer: A national cancer registry study from the Czech Republic and review of the literature - Whitley, Adam; Kocián, Petr; Nikov, Andrej; Krejčí, Denisa; Pehalová, Lucie; Blaha, Milan; Dušek, Ladislav; Gürlich, Robert (Journal of hepato-biliary-pancreatic sciences, 2023)
BACKGROUND: The aim of this study was to compare trends in mortality and incidence, clinicopathological features and survival of patients diagnosed with pancreatic ductal adenocarcinoma under 50 years of age (early-onset pancreatic cancer [EOPC]) with patients diagnosed over 50 years of age (late-onset pancreatic cancer [LOPC]). METHODS: The national oncological registry of the Czech Republic was reviewed to identify all patients with histologically confirmed pancreatic ductal adenocarcinoma diagnosed between the years 1985 and 2015. Incidence, mortality, clinicopathological and survival data were analyzed and compared between patients with EOPC and LOPC. RESULTS: From a total of 18 888 patients included in the study, 1324 patients were under the age of 50 years (7.0%). The average annual percentage changes (AAPC) in incidence of all patients with EOPC was -1.0%. The APPC for male patients with EOPC was -2.0% and for female patients was +0.6%. The AAPC in incidence for LOPC was +1.3%. There were no differences in tumor stage, grade or location between EOPC and LOPC. Young patients were more frequently male (64.4% vs. 52.9%), more frequently underwent treatment and had better overall survival. The median survival interval for EOPC was 5.9 months and for LOPC was 4.5 months (p < .001). CONCLUSIONS: The clinicopathological features of pancreatic ductal adenocarcinoma were similar in patients under and over the age of 50 years. Patients with EOPC survived longer than patients with LOPC. Continued efforts should be made to diagnose early and treat young patients aggressively.
Keywords: Middle Aged; Czech Republic; Carcinoma, Pancreatic Ductal; lidé; Pancreatic Neoplasms; nádory slinivky břišní; Incidence; Registries; Humans; incidence; Male; mužské pohlaví; duktální karcinom slinivky břišní; Česká republika; registrace; lidé středního věku; ženské pohlaví; Female